STRUCTURAL AND FUNCTIONAL CHANGES IN HIPPOCAMPAL NEURONS AFTER SURGERY UNDER ANESTHESIA WITH SEVOFLURANE (experimental research) - G. Yu. Yukina; V. V. Tomson; Yu. S. Polushin; I. V. Belozertseva; A. Yu. Polushin; V. O. Krivov; S. N. Yanishevskiy (Вестник анестезиологии и реаниматологии, 2018)
Hippocampus plays an important role in the cognitive mnestic functions. It coordinates emotional process, defines the intensity and specificity of behavioral, neuron and hormone reactions. Structural changes in hippocampus neurons can result in learning and memory disorders. The objective: to investigate morphometric parameters of hippocampus fields in rats after abdomen surgery with exposure to sevoflurane. Subjects and methods. The experimental research was performed using Wistar rats (n = 15). Rats from the experimental group (n = 7) had abdomen surgery with anesthesia with sevoflurane with the consequent continuous exposure to it (6 hours, 2 vol. % of sevoflurane, air flow – 1 l/min.). During 21 days rats from both groups had a number of behavioral tests. In 12 hours after the last behavioral test (on the 22-th day after the start of the experiment) the rats were decapitated with consequent brain extraction. The obtained materials were fixed in 10% neutral formalin on phosphate buffer (pH 7.4) for 24 hours minimum. Preparations of CA1, Ca2, Ca3, and Ca4 fields were studied under light microscope DM-750 (Leica, Germany) using the computer image analysis software of ImageScope M with 400-fold magnification. Results. The tests showed that cytoarchitectonics of hippocampus field was intact, pyramidal neurons had a large rounded nucleus with one, two or more distinct nucleoli. No pericellular and perivascular edema was detected. In the experimental group, all fields of the hippocampus had structural and functional changes. It manifested through both quantitative and qualitative signs of neuronal damage, especially in the Ca1 field. Segments of pyramidal neurons were disorganized, morphologically modified neurons were found: hyperchromatic shriveled neurons with no nucleus or poorly visible nucleus of the irregular shape. The appearance of morphologically changed neurons and disorganization of hippocampal layers led to changes in the width of pyramidal neurons segments. Conclusion. Morphological changes of hippocampal structures of rats after surgery and anesthesia may be the cause of cognitive functions decline during the postoperative period.